Multiple myeloma invasion of the central nervous system - Marjanović Slobodan; Mijušković Zoran; Stamatović Dragana; Mađaru Lavinika; Ralić Tijana; Trimčev Jovana; Stojanović Jelica; Radović Vesna (Vojnosanitetski Pregled)
Introduction. Multiple myeloma (MM) is characterized by the presence of neoplastic proliferating plasma cells. The tumor is generally restricted to the bone marrow. The most common complications include renal insufficiency, hypercalcemia, anemia and reccurent infections. The spectrum of MM neurological complications is diverse, however, involvement of MM in the cerebrospinal fluid (CSF) and leptomeningeal infiltration are rare considered. In about 1% of the cases, the disease affects the central nervous system (CNS) and presents itself in the form of localized intraparenchymal lesions, solitary cerebral plasmocytoma or CNS myelomatosis (LMM). Case report. We presented the clinical course of a 55-year-old man with MM and LMM proven by malignant plasma cells in the CSF, hospitalized with the pain in the thoracic spine. His medical history was uneventful. There had been no evidence of mental or neurological impairment prior to the seizures. Physical examination showed no abnormalities. After a complete staging, the diagnosis of MM type biclonal gammopathia IgG lambda and free lambda light chains in the stage III was confirmed. The treatment started with systemic chemotherapy (with vincristine, doxorubicin plus high-dose dexamethasone - VAD protocol), radiotherapy and bisphosphonate. The patient developed weakness, nausea, febrility, dispnea, bilateral bronchopneumonia, acute renal insufficiency, confusions, headaches and soon thereafter sensomotor aphasias and right hemiparesis. The patient was treated with the adequate therapy including one hemodyalisis. His neurological status was deteriorated, so Multislice Computed Tomography (MSCT) of the head was performed and the findings were normal. Analysis of CSF showed pleocytosis, 26 elements/ mL and increased concentrations of proteins. Cytological analysis revealed an increased number of plasma cells (29%). Electrophoretic analysis of proteins disclosed the existance of monoclonal components in the serum, urine and CSF. Immunofixation electrophoretic and quantitative nephelometric tests confirmed Biclonal multiple myeloma of IgG lambda and light chain lambda isotypes. Analysis of neurothropic viruses with ELISA methods was negative. Once the presence of LMM was confirmed, the patient received intrathecal chemotherapy with methotrexate, cytosine arabinoside, dexamethasone three times a week, and systemic high doses of dexamethasone iv like a single agent without craniospinale irradiations. Despite the treatment, the patient died one month after the diagnosis. Autopsy was not performed. Conclusion. Presented patient, as well as most other patients with MM progressing to CNS infiltration was in the stage III. In addition to the detailed clinical examination, and all investigations required for MM diagnosis and staging of the disease, we introduced the additional CSF examination and calculation of kappa lambda ratio, that helped us make an early diagnosis and prognosis of MM with LMM. Although LMM had a low prevalence, it could be more frequent than expected especially in patients with high risk. CSF examination with positive plasma cells and abnormal morphology remains the hallmark for diagnosing CNS infiltration.